Postprandial gastric function in pancreatic insufficiency. Issue 3 (March 1979) - Regan, P T; Malagelada, J R; Dimagno, E P; Go, V L
Abstract : Abnormalities in postprandial gastric function could contribute to the maldigestion of pancreatic insufficiency. To measure simultaneously postprandial gastric secretion and emptying and correlate these measurements with intraluminal duodenal changes, we performed intestinal intubation and duodenal perfusion during feeding of a solid-liquid test meal in 10 healthy controls and 10 patients with documented pancreatic insufficiency before and after replacement therapy. In pancreatic insufficiency, intraduodenal pH was significantly decreased late in the postprandial period while simultaneously measured duodenal acid loads were normal, confirming that reduced bicarbonate output rather than increased acid delivery was responsible for higher duodenal acidity in these patients. Significant (P less than 0.05) reductions in postprandial acid, pepsin, and total secretory outputs were noted in untreated patients only during the first postprandial hour. Absolute gastric emptying rates were lower in patients (P less than 0.05) than in healthy subjects, but fractional rates of emptying were similar. Fasting and postprandial hypergastrinaemia were consistently observed in the patients with pancreatic disease. There are postprandial disturbances of secretory function but no primary gastric motor defect in patients with exocrine pancreatic insufficiency.